2014
DOI: 10.1038/ijo.2014.176
|View full text |Cite
|
Sign up to set email alerts
|

Natural course of metabolically healthy abdominal obese adults after 10 years of follow-up: the Tehran Lipid and Glucose Study

Abstract: MHAO is a relatively unstable condition and a considerable percentage of these individuals will lose their metabolic health as time passes. Baseline metabolic characteristics may be useful predictors of this change and should be considered in the care of these individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 41 publications
4
69
1
8
Order By: Relevance
“…MHO class II without any metabolic abnormality did not significantly increase the risk of CACS progression even after adjusting for possible confounders. By contrast, MHO class I, which has been frequently defined in previous studies [2427,29,30], showed a 1.7-fold higher risk for CACS progression than non-obese metabolically healthy subjects. A stratified analysis of this MHO class I group according to the number of metabolic abnormality (that is, 0 or 1) showed that there was a significant difference in the risk of CACS progression between MHO subjects with no metabolic abnormality and one metabolic abnormality at the baseline.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…MHO class II without any metabolic abnormality did not significantly increase the risk of CACS progression even after adjusting for possible confounders. By contrast, MHO class I, which has been frequently defined in previous studies [2427,29,30], showed a 1.7-fold higher risk for CACS progression than non-obese metabolically healthy subjects. A stratified analysis of this MHO class I group according to the number of metabolic abnormality (that is, 0 or 1) showed that there was a significant difference in the risk of CACS progression between MHO subjects with no metabolic abnormality and one metabolic abnormality at the baseline.…”
Section: Discussionmentioning
confidence: 78%
“…Abdominal obesity was defined as WC ≥ 90 cm for men and ≥ 80 cm for women according to the International Obesity Task Force criteria for the Asian-Pacific population [23]. MHO was defined according to the most frequently used definition in recent studies (MHO class I) [2427]. Briefly, obese participants who met ≤ 1 of the following National Cholesterol Education Program–Adult Treatment Panel III (NCEP–ATP III) criteria for metabolic syndrome [28] were considered to have MHO class I: (a) TG level ≥ 1.7 mmol/L (150 mg/dL); (b) HDL cholesterol level < 1.0 mmol/L (40 mg/dL) in men and < 1.3 mmol/L (50 mg/dL) in women; (c) blood pressure ≥ 130/85 mmHg or intake of antihypertensive medication; and (d) fasting glucose level ≥ 5.6 mmol/L (100 mg/dL) or intake of anti-diabetic medication.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies suggest that metabolically healthy individuals may be younger than their metabolically unhealthy counter parts suggesting that over time, they too will develop CVD [25,26]. Additionally, the conversion of MHO to the higher risk MUO over time may explain this effect, as in 2 studies, MHO was seen to convert to MUO in 34.2% [27] and >50% of subjects over prolonged follow-up [28].…”
Section: Is Mho a "Benign" Phenotype?mentioning
confidence: 93%
“…Through use of repeated measures of metabolic and obesity statuses on the same individuals over time, studies have shown that after 6 years of follow-up, about one-third of initially healthy obese adults had become unhealthy obese (30,60); others report that after 7-10 years this proportion is nearly half (58,(61)(62)(63); and after 20 years this figure is just over half (59). The proportion of healthy obese adults who progress to unhealthy obesity appears larger with longer follow-up periods, indicating that the tendency to progress gets stronger with time.…”
Section: Is Healthy Obesity Harmless?mentioning
confidence: 99%